Maternal Nutrition, Body Composition and Gestational Weight Gain on Low Birth Weight and Small for Gestational Age-A Cohort Study in an Indian Urban Slum - Raja Sriswan Mamidi; Santosh Kumar Banjara; Sridevi Manchala; Ch Khadar Babu; J. J. Babu Geddam; Naveen Kumar Boiroju; Bhaskar Varanasi; G. Neeraja; G. Venkat Raji Reddy; B. A. Ramalakshmi; R. Hemalatha; Gargi Meur (MDPI AG, 2022)
Maternal nutritional status and care during pregnancy are essential for adequate birth weight. In this prospective cohort study (N = 1061) in an urban slum, we investigated the association of maternal anthropometry, body composition, gestational weight gain and dietary intakes with low birthweight (LBW, <2.5 kg). About one-third of the women were short (<150 cm), 35% were underweight (<45 kg), 23% suffered from chronic energy deficiency (CED, BMI < 18.5 kg/m2) and another 30% were overweight/obese. The mean age and BMI were 23 years and 21.7 kg/m2, respectively, and haemoglobin was 10.73 g/dL. The mean birthweight (N = 605) was 2.81 ± 0.5 kg, and the average gestational age was 38 ± 2 weeks. About 15% of infants had LBW, and 48% were small for gestational age (SGA). Maternal body composition was assessed by skinfold thickness (SFT) in all trimesters. In the first trimester (N = 762), we found that mean fat-free mass (FFM), fat mass (FM) and body fat percentage (% BF) were 38.86 kg, 11.43 kg and 21.55%, respectively. Low birthweight was significantly associated with preterm deliveries (p < 0.001) and less fat free mass (p = 0.02) in the third trimester. Among other factors were age (p = 0.017), maternal anthropometry (height: p = 0.031; weight: p = 0.059) and fewer antenatal check-ups (p = 0.037). Small size (SGA) was consistently associated with maternal bodyweight at all trimesters (term I, p = 0.013, term II, p = 0.003 and term III, p < 0.001), fat mass in the third trimester (p < 0.001) and maternal height (p = 0.003).